Honduras - Development Policy Review : Accelerating Broad-based Growth - World Bank (Washington, DC, 2013)
This Development Policy Review (DPR) discusses Honduras's development agenda with a special focus on accelerating economic growth. This focus emerges from the Honduras Poverty Reduction Strategy Paper (PRSP), which identified growth as the main determinant o f the evolution of poverty, and guides the review of policy developments in various economic, social and infrastructure sectors. To the extent that the measures and reforms recommended in this report are able to generate a more attractive investment climate in Honduras, they will clearly serve to promote a faster accumulation o f physical capital, which is one component of economic growth. The main thrust of most of these reforms, however, is to improve the quality of factor services and the efficiency of factor allocation, which, in a growth accounting framework, are reflected in faster productivity growth. Recommended are measures to expand the coverage and quality o f education, measures to promote financial market development, measures to remove price distortions, attract greater private investment and improve the regulatory framework, as well as measures contemplated on the governance front, especially in the area o f improving public sector financial management and the civil service.